Frame-based stereotactic biopsies of brainstem lesions: monocentric comparison of the transfrontal and the suboccipital-transcerebellar approach over a 16-year period - Kaes, Manuel; Neumann, Jan-Oliver; Beynon, Christopher; Naser, Paul; Kiening, Karl; Krieg, Sandro; Jakobs, Martin (Neurosurgical review, 2024)
Both the transfrontal and the suboccipital-transcerebellar approach are frequently used trajectories for frame-based stereotactic biopsies of brainstem lesions. Nevertheless, it remains unclear which approach is more favorable in terms of complications, diagnostic success and outcome, especially considering the location of the lesion within the brainstem. This study compared the safety and diagnostic yield of these two approaches. Furthermore, a brainstem zone model was created to answer the question, whether there is a favorable approach depending on the location of the lesion in the brainstem. A retrospective analysis of 84 consecutive cases of frame-based stereotactic biopsies for brainstem lesions via either transfrontal or suboccipital-transcerebellar approaches over a 16-year period was performed. Clinical and surgical data regarding trajectories, histopathology, complications and outcome was collected. The brainstem was divided in anatomical zones to compare the use of the two approaches depending on the location of the lesions. A total of n = 84 cases of stereotactic biopsies for brainstem lesions were performed. In 36 cases the suboccipital-transcerebellar approach was used, while in 48 cases surgery was performed via the transfrontal approach. The patient’s demographic data were comparable between the two approaches. Overall diagnostic yield was 90.5% (93.8% transfrontal vs. 86.1% suboccipital, p = 0.21, Risk Difference (RD) 0.077, CI [-0.0550, 0.2090]). Complications occurred in 11 cases (total complication rate: 13.1%; 12.5% transfrontal vs. 13.9% suboccipital, p = 0.55, RD 0.014, CI [-0.1607, 0.1327]). The brainstem model showed a more frequent use of the suboccipital approach in lesions of the dorsal pons. The transfrontal approach was used more frequently in mesencephalic targets. No significant differences in terms of complications and diagnostic yield were observed, even though complications in medullary lesions appeared higher using the transfrontal approach. This study showed, that if the approaches are used for their intended target locations there are no significant differences between the transfrontal and the suboccipital-transcerebellar approach for frame-based stereotactic biopsies of brainstem lesions in terms of diagnostic yield and safety. Therefore, our data suggests that both approaches should be considered for stereotactic biopsy of brainstem lesions.
Gesehen am 21.03.2025